The Link between Firm-Level Productivity and Decisions to Export – the Case of Lodz Voivodeship - Gabrielczak, Piotr; Serwach, Tomasz (Theory, Methodology, Practice – Review of Business and Management, 2014)
The aim of this article is to test whether there are differences in productivity between exporters and non-exporters among manufacturing firms from Lodz Voivodeship. Not only do we look for a correlation, but also we verify two main hypotheses about the causality of the postulated relation: self-selection and learning-by-exporting (LBE). We use microeconomic data from the Central Statistical Office of Poland and the Olley-Pakes algorithm to estimate the total factor productivity (TFP) of firms. Then we apply that data to probit and logit estimations of export status and examine TFP increments of new exporters. We did not find sound evidence for self-selection among firms in Lodz Voivodeship. We managed, however, to prove the existence of an LBE effect, though this effect seems to be weak and restricted to certain sectors with comparative advantages. One should keep in mind that our research was limited by data availability and further studies are required. However, this study is a rare example of a regional analysis of international trade and deals with main New New Trade Theory postulates in a complex manner.